The Role Of Human Capital Development And Sustainable Leadership In Building Adaptive Organizations In The Sustainability Era - Vina Riza Nurillah; Toni Herlambang; Feti Fatimah (International Journal of Education Management and Religion, 2026)
In the sustainability era marked by environmental uncertainty, technological disruption, and global socio-economic transformation, organizations are increasingly required to build adaptive capacities that ensure long-term resilience. The research aims to analyze how human-centered capability development and value-based leadership interact to create organizational adaptability that integrates economic, social, and ecological priorities. This study employs a qualitative descriptive method, collecting data through semi-structured interviews, document analysis, and observation within sustainability-oriented institutions. Data were analyzed using Miles and Huberman’s interactive model, encompassing data reduction, display, and conclusion drawing to interpret the interrelation between leadership, learning culture, and adaptive behavior. The findings reveal that Human Capital Development serves as the structural foundation that enhances innovation, learning agility, and employee empowerment, while Sustainable Leadership functions as the ethical compass that guides these human capacities toward responsible and forward-looking transformation. The integration of both elements generates a resilient, learning-oriented, and value-driven organizational ecosystem that continuously adapts to environmental, social, and technological shifts. In conclusion, the research emphasizes that adaptability in the sustainability era is a human-driven process grounded in continuous learning, ethical leadership, and systemic alignment. Organizations that invest in human capital and adopt sustainability-based leadership models demonstrate stronger resilience and competitiveness. These results contribute theoretically by integrating Dynamic Capability Theory and Sustainability Leadership Framework, and practically by offering a conceptual roadmap for organizations aiming to embed sustainability into their adaptive management systems.